High pre-transplant serum nitrate levels predict risk of acute steroid-refractory graft-versus-host disease in the absence of statin therapy - Dietrich, Sascha; Okun, Jürgen G.; Schmidt, Kathrin V.; Falk, Christine Susanne; Wagner, Andreas H.; Karamustafa, Suzan; Radujković, Aleksandar; Hegenbart, Ute; Ho, Anthony Dick; Dreger, Peter; Luft, Thomas (Haematologica, 2014)
Steroid-refractory graft-versus-host disease is a life-threatening complication after allogeneic stem cell transplantation. Evidence is accumulating that steroid-refractory graft-versus-host disease is associated with endothelial distress. Endothelial cell homeostasis is regulated by nitric oxide, and serum nitrates are derived from nitric oxide synthase activity or dietary sources. In this retrospective study based on 417 patients allografted at our institution we investigated whether quantification of serum nitrates could predict steroid-refractory graft-versus-host disease. Elevated pre-transplant levels of serum nitrates (>26.5 μM) predicted steroid-refractory graft-versus-host disease (P=0.026) and non-relapse mortality (P=0.028), particularly in combination with high pre-transplant angiopoietin-2 levels (P=0.0007 and P=0.021, respectively). Multivariate analyses confirmed serum nitrates as independent predictors of steroid-refractory graft-versus-host disease and non-relapse mortality. Differences in serum nitrate levels did not correlate with serum levels of tumor necrosis factor or C-reactive protein or expression of inducible nitric oxide synthase in blood cells. Patients with high pre-transplant nitrate levels had significantly reduced rates of refractory graft-versus-host disease (P=0.031) when pravastatin was taken. In summary, patients at high risk of developing steroid-refractory graft-versus-host disease could be identified prior to transplantation by serum markers linked to endothelial cell function. Retrospectively, statin medication was associated with a reduced incidence of refractory graft-versus-host disease in this endothelial high-risk cohort.